Pelatihan Pembuatan Penjernih Air yang Konstruktif Sebagai Upaya Memutus Penyebaran Covid-19 di Desa Kalosi Alau Kabupaten Sidenreng Rappang - Asmah Adam; Bakhrani A Rauf; Panennungi T (Seminar Nasional LP2M UNM, 2022)
Abstract. This social work aimed to improve: (1) partner’s knowledge constructive water filter (2) partner’s skill to design constructive simple water filter and (3) the skill to construct constructive water filter. The methods that used of this social work were: (1) to improve the knowledge of people about the constructive water filter then the discourse, interactive and discussion method are conducted, (2) to improve their skill to design the constructive water filter then methods discourse, interactive, discussion, and demonstration are conducted and (3) to improve the skill to make the constructive water filter then discourse, interactive, discussion, demonstration, and training methods are conducted. The results of social work, (1) the material of workshop was responded by people because of constructive water filter was easy to be made and the compound could be gained in workshop location; (2) constructive water filter could be accepted, understood, and followed by people technically; (3) the people was highly motivated to follow these activities; (4) the people were ready to make their own constructive water filter in their house and inform to others.  Keywords: Workshop, Filtration, Water